Putting power and politics central in Nepal’s water governance - Suhardiman, Diana; Karki, Emma; Bastakoti, Ram C. (Wiley, 2021)
Motivation: Power relations, and the politics shaping and reshaping them, are key to determining influence and outcomes in water governance. But current discourse on water governance tends to present decision-making as neutral and technical unaffected by political influences.